Beplanning vir die voetgangerbeweging van die visueel gestremde - van Zyl, FDW; Matthysen, P (Acta Structilia, 1994)
The obstructions with which the visually impaired pedestrian can get on his routes can be categorized as obstacles and danger points. Hazards can be eliminated by simple and relatively inexpensive modifications. Obstacles can be overcome with the correct long-dress technique, but it has a major influence on the walking speed of the visually impaired. This statement is shown by means of a step-by-step experiment. *This article is written in Afrikaans.